Video assisted thoracoscopy surgery a viable alternative for duplication cyst excision: a case report on foregut duplication cyst - C., Anjana; Priya, A.; Yadav, Arun Chander (International Journal of Basic & Clinical Pharmacology, 2024)
Alimentary tract duplication is a relatively uncommon congenital abnormality. It can be found anywhere from the mouth to the anus and can be symptomatic or undetectable. Although congenital duplication can happen anywhere in the gastrointestinal tract, the ileum, oesophagus, and colon are the most common locations. The foregut, which includes the stomach, and first and second segments of the duodenum, is the source of one-third of all duplications. When foregut duplication involves the bronchial tree, respiratory symptoms are often present. Furthermore, excision through surgery is required for pathological examination of the resected specimen for definitive diagnosis. The most promising surgical approach for cyst excision has been thought to be open surgical resection through a posterolateral thoracotomy incision. However, video assisted thoracoscopy surgery has recently emerged as a viable surgical option for duplication cyst removal In paediatric surgery, video assisted thoracoscopy surgery has been established to facilitate the removal of mediastinal masses. However there is a limitation of research in the literature regarding the best surgical technique for oesophageal duplication cyst excision. In girls, foregut duplication is more common, especially in cases when bronchopulmonary involvement is present. While many duplications result in issues in early development, some are discovered by accident. When foregut duplication involves the bronchial tree, respiratory symptoms are often present. Haemoptysis and respiratory distress may be present in specific cases of the patient. Here, we described a 5-year-old male infant’s case of foregut duplication with bronchial involvement and its management.